Jewish Bialystok and its diaspora - Kobrin, Rebecca (Modern Jewish experience (Bloomington, Ind.), 2010)
Kobrin's study of the dispersal of Jews from one city in Poland demonstrates how the act of migration set in motion a wide range of transformations that led the migrants to imagine themselves as exiles not only from the mythic land of Israel but most immediately from their east European homeland.